Comparison of Laparoscopic and Open Live Donor Nephrectomy - Hashmi, Syed Daood; Razik, Sohail; Aziz, Majid; Naeem, Muhammad; Ali, Muhammad; Saeed, Bilal (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare laparoscopic live donor nephrectomy with open live donor nephrectomy.Study Design: Cross Sectional Analytical Study.Place and Duration of study: Armed Forces Institute of Urology, from May 2023 to Apr 2024Methodology: With non-probability consecutive sampling technique, the patients who presented in OPD between May 2023 and April 2024 and underwent live donor nephrectomy were selected by non-convenience sampling technique. The kidney donors were divided into two groups: Group A -those scheduled for open donor nephrectomy and Group B - those receiving laparoscopic donor nephrectomy.Results: There were 22 donors each group. The donors' ages varied from 36 to 59 years, with an average age of 47.75+5.29 years. In the participating group were thirty males and fourteen females. Study involved the performance of 7 right-sided donor nephrectomies (RDN) and 37 left-sided donor nephrectomies (LDN). In cases with Group B, the average length of the procedure was noticeably longer. Furthermore, the initial warm ischemia in Group B - lasted an average of 9.43 + 1.93 minutes, a significantly longer time than in Group A (4.04+1.21 minutes). It was determined that this difference was statistically significant.Conclusion: Our study concluded that laparoscopic donor nephrectomy showed advantages including less discomfort after surgery, a faster recovery period, and comparable results for graft function when compared to open live donor nephrectomy. These results imply that laparoscopic donor nephrectomy is a practical and well-liked procedure, which adds to its growing acceptance in the medical community.